Desain Pintu Air Berbantu Komputer Untuk Saluran Irigasi Tersier di Daerah Irigasi Cikarawang Bogor: Computer-Aided Design Water Gate for Tertiary Irrigation Channels in Bogor-Cikarawang Irigation Area - Sulaecha, Eka; Setiawan, Budi Indra (Departemen Teknik Sipil dan Lingkungan IPB, 2020)
Irrigation water gate was one of the supporting components of agricultural activities, especially the management of rice fields, because it was utilized in the management of water flow. The implementation of water gate has a complex and interdependent set of tasks. So that was the problem which can made undesired effects. So that, the planning can be shorted by computer design . Besides, the changes in a design could be overcome quickly and precisely. The purpose of this research is to the effective rainfall, evapotranspiration, discharge of irrigation water needs in the Cikarawang irrigation area, produce a design of computer-aided water gate, and know RAB for the construction of the water gate. The study was conducted from April to July 2020. The place to do the research was Cikarawang Village, Bogor Regency, West Java. The results of the study were the design of water gate by using data plotting with computer-aided script files (SCR). The effective rainfall of 1806.3 mm, the highest evapotranspiration of 5.5 mm/day and the lowest evapotranspiration of plants at 4 mm/day, the highest irrigation water demand was 2.18 lt/dt/ha, The dimensions of 0.5 x 0.75 x 0.012 m, and water gate opening 0.27 m. These water gate openings were used when the plant's water requirements are highest. The cost of making water gate made from fiberglass is Rp. 838.000,-while for steel costs Rp. 3.500.000,-.